Energy and power estimation for three different locations in Palestine - Ahmed S A Badawi; Nurul Fadzlin Hasbullaha; Siti Hajar Yusoff; Aisha Hassan Hashim (Institute of Advanced Engineering and Science, 2019)
In this paper power energy estimated based on wind speed records in three different areas in Palestine Nablus, Ramallah and Gaza. The main aims of this study to calculate the total amount of power and energy that can produce and to encourage investment in renewable energy in Palestine. Available meteorological data from local weather stations are used to study the wind energy potential in the West Bank (WB) for two sites and Gaza Strip (GS) for one site. The daily average wind speed data for three sites in Palestine analyzed, and fitted to the Weibull probability distribution function. The parameters of Weibull have been calculated by author using Graphical method. This study shed lights on the relationship between the wind energy and power versus the mean wind speed (MWS). The total gathered energy per unit area during 2006 in WB from Nablus site is 927.1 kwhr/m2, whereas 2008.0141 kwhr/m2 from Ramallah site.This significant study to assess the wind energy production in Palestine to encourage investment in renewable energy sectors.